Pretreatment of aluminium alloy milling wastewater by micro-electrolysis process. Issue 3 (May 2019) - Li, Ru; Huang, Xin; Gu, Junli
Abstract: The aluminium alloy milling wastewater belongs to high concentration organic alkaline wastewater, the pH value is up to 13-14, and the COD concentration is 3000mg/L-3300mg/L, if direct discharge into water bodies without harmless treatment can seriously endanger the ecological environment and human health. In this study, the micro-electrolysis process was used to pre-treat the aluminium alloy milling wastewater, and the COD removal rate was the indicator. Under the condition that the mass ratio of iron to carbon is 1:2, the dosage of iron is 67g/L, the pH is 3, and the reaction time is 60min, the average removal rate of COD in aluminium alloy milling wastewater can reach 71.34%. The kinetic analysis of the process of pre-treatment of aluminium alloy milling wastewater by micro-electrolysis process is in accordance with the first-order kinetic model. The dynamic equation is: C t = C 0 exp ( − 3.5762 C 0 − 0.6351 t ) .